واقع وأهمية الصكوك المالية الإسلامية بالأسواق المالية الدولية (دراسة حالة السوق المالي الماليزي) - تجاني, محمد العيد; دادن, عبد الغني (جامعة الوادي - University of Eloued, 2015)
نحاول من خلال دراستنا هذه إبراز الدور الهام الذي يمكن أن تلعبه الصكوك المالية الإسلامية في تحقيق ما تطمح إليه الدول الناشئة وشعوبها من تقدم ونهضة واستقرار، وإن إقبال المتعاملين على هذه الصكوك لخير دليل على ذلك، حيث أصبحت الصكوك الإسلامية خاصية ملازمة لتطور وتنشيط الأسواق المالية الدولية في السنوات الأخيرة، خاصة في بلادنا العربية والإسلامية، وكانت بمثابة الطاقة التي دفعت بها نحو النمو و التطور من خلال توفير المعالم المؤدية إلى تكوين أسواق مالية تتعامل بمنتجات مالية على أساس الشريعة السمحى، وذلك من خلال آلياته التي عملت على استبدال سعر الفائدة الدائن والمدين بنظام المكافأة لصاحب المال باستعمال صيغ تمويلية تقوم على أساس مبدأ المشاركة أو على أساس الأجر والثواب، كما تستخدم الصكوك الإسلامية في دعم التنمية الاقتصادية والتقدم الاجتماعي للشعوب والمجتمعات في الدول الناشئة والإسلامية وفقًا لمبادئ وأحكام الشريعة الإسلامية، وبالتالي يمكن أن نقول أن الأسواق المالية الدولي ستستفيد الكثير من خلال إقدامها على إصدار صكوك الاستثمار الإسلامية، التي أصبحت مطلب العديد من المؤسسات والحكومات. showing clearly by our study of the important role that can be played by Islamic investment instruments in achieving the ambitions of emerging countries and its peoples of progress and renaissance and stability, whereas welcoming of the Muslim masses and a High demand to deal with these instruments for the best proof of that, where Islamic instruments have become an inherent characteristic of the development and revitalization of emerging financial markets in recent years, Especially in the Arab and Muslim countries, and has served as the energy that pushed it out towards the growth and development through the provision of milestones that leading to the formation of financial markets deal financial products based on Sharia samha, through mechanisms that have worked to replace the interest credit rate and the debtor reward system for the owner of money using funding formulas based on the principle of participation, or on the basis of pay and reward, As Islamic instruments are also used to support economic development and social progress of the peoples and communities in emerging and Islamic States in according to the principles and provisions of Islamic law, therefore we can say that the financial emerging markets will benefit a lot through issuing the Islamic investment instruments, which became a requirement many institutions and governments.
مقال
Keywords: الأسواق المالية الدولية، الصكوك الإسلامية; international financial markets, Islamic instruments.